2016
DOI: 10.1111/izy.12143
|View full text |Cite
|
Sign up to set email alerts
|

The welfare of wild animals in zoological institutions: are we meeting our duty of care?

Abstract: Across the world there are many different species of wild animals maintained in zoological institutions of one sort or another for a variety of purposes. Their welfare is directly dependent upon the quality of life they experience, which in turn is driven by the understanding the owner/keeper has of the needs of the animals. This ‘understanding’ may or may not be informed by scientific knowledge. Sub‐optimal conditions and/or husbandry practices can result in injury, disease and poor mental health; hence, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…The auditors are experienced members of the WW team with extensive international experience in captive animal management and welfare. The primary purpose of the audit is providing an aide memoire for auditors, auditing against the WW Core Fundamentals Standard [ 34 ], rather than use as a research tool. The audit comprises 110 questions relating to (i) nutritional provision (nutrition), (ii) the environment in which the animals are housed (environment), (iii) animal health, (iv) animal behaviour (behaviour), (v) the perceived mental state of the animals (mental health), (vi) the standard of animal record keeping (record keeping), (vii) staff health and safety (health and safety), (viii) information relating to the personnel working at the zoo (personnel) and (ix) other (containing questions pertaining to financial support and waste disposal).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The auditors are experienced members of the WW team with extensive international experience in captive animal management and welfare. The primary purpose of the audit is providing an aide memoire for auditors, auditing against the WW Core Fundamentals Standard [ 34 ], rather than use as a research tool. The audit comprises 110 questions relating to (i) nutritional provision (nutrition), (ii) the environment in which the animals are housed (environment), (iii) animal health, (iv) animal behaviour (behaviour), (v) the perceived mental state of the animals (mental health), (vi) the standard of animal record keeping (record keeping), (vii) staff health and safety (health and safety), (viii) information relating to the personnel working at the zoo (personnel) and (ix) other (containing questions pertaining to financial support and waste disposal).…”
Section: Methodsmentioning
confidence: 99%
“…Wild Welfare [ 32 ] is a charity working globally to improve welfare for wild animals living in captivity and has a welfare auditing system, based on the Five Domains, that is carried out before any intervention occurs [ 33 ]. Utilizing their pre-intervention audit, the aim of this research was to investigate if there were common welfare concerns associated with zoo animal provision across a number of developing country zoos, identifying the possible reasons behind these and considering strategies which can be utilized for improving zoo animal welfare.…”
Section: Introductionmentioning
confidence: 99%
“…comm, October 2015) such as those outlined in Caring for wildlife, the WAZA animal welfare strategy [ 1 ]. The field of zoo animal welfare science has developed significantly over recent years [ 1 , 2 , 14 ], however these developments often seem to be region-specific and it is possible that as zoos in the Western world embrace technology and science in the assessment and improvement of animal welfare, we may further increase the distance between the activities and standards of the global zoo community as many countries struggle to provide good zoo animal welfare [ 15 ]. It may also be suggested that because of the varying standards of zoos around the world, the concept of a ‘Global zoo community’ is a challenging one, but in terms of assessing ‘standards’, the distinction is not so simple as accredited versus non-accredited zoos.…”
Section: Zoo Animal Welfarementioning
confidence: 99%
“…Such zoos are more likely to be located in countries where resources to provide for zoo animal welfare are restricted, and where technological and research advances in the fields of zoo animal welfare science and enrichment are limited. Whilst specific capacity-building of zoo professionals can be impactful [ 15 , 16 ], there are also cultural, resource-based and knowledge limitations: Knowledge of the diverse and complex needs of the species housed in zoos may contribute one barrier to the ability of zoos to provide good animal welfare [ 17 ]. Developments in animal welfare science have historically been biased towards the agricultural industry [ 18 , 19 ], whilst animal welfare in zoos has relied upon taking remedial action, once indicators of poor welfare are identified in zoo animals [ 17 ].…”
Section: Zoo Animal Welfarementioning
confidence: 99%
“…Animal welfare is an all-encompassing concept and notoriously hard to measure, where the most accurate approach is to collect behavioral, physiological and cognitive data over a period of time and then weight the results to achieve some sort of meaningful overall picture of welfare [ 9 , 11 , 67 , 68 ]. Although modern zoos report that good animal welfare is a priority and central to their purpose [ 69 ], they often do not have the time or resources to measure welfare continuously and scientifically [ 70 , 71 ], bearing in mind that this is still a relatively new branch of science [ 9 ]. The application of cognitive bias testing to animals has been the one of the most significant discoveries in the last decade for animal welfare science due to its feasibility and success in reflecting affective states [ 36 , 72 ].…”
Section: Why Should Zoos Conduct Cognitive Bias Research?mentioning
confidence: 99%